If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -4 = -5.6 Reorder the terms: -4 + X = -5.6 Solving -4 + X = -5.6 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + X = -5.6 + 4 Combine like terms: -4 + 4 = 0 0 + X = -5.6 + 4 X = -5.6 + 4 Combine like terms: -5.6 + 4 = -1.6 X = -1.6 Simplifying X = -1.6
| -2x^3+3x^2-x-36=48 | | -2x^3+3x^2-x-36=38 | | -2x^3+3x^2-x-36=36 | | -2x^3+3x^2-x-36=24 | | -3x-2x=7 | | 2b+17=41 | | 32x^2-34+40=0 | | 18x-xy+7x=5x+20 | | -7(4+6k)=-4(9x-11)+9 | | 5cosX+6=4 | | 3y-5=0.5*4y+2 | | -5n+3(3+7n)= | | a(n)=n+0.6(n-1) | | (3+3)-3= | | -x-9=6x+5 | | a(21)=-1.4 | | (3+a)-3= | | 2.4=6f | | 8x=4x+48 | | 4x+2x=5x+x | | 4p-4=6p-4-2p | | 3x+4x+2x+x=360 | | 2.4=6.4 | | -x-9=-6x+5 | | Logx=0.55 | | .35x+8=21 | | 6x^2+3x+-180=0 | | 3+2.4x=1 | | 4x+4(x+7)=128 | | p=-5.4+-0.4q | | x+123456789=0 | | (6*n)+n=56 |